2022
DOI: 10.1109/access.2022.3183223
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band On-Body Near Field Antenna for Measuring Deep Core Temperature With a Microwave Radiometer

Abstract: Deep core temperature is the most basic and important information about health conditions. The non-contact infrared thermometer is widely used to measure the temperature of the human body. However, the infrared thermometer cannot measure the deep core temperature. To overcome this limitation, measuring deep core temperature with a microwave radiometer is gaining attention. In this study, we propose a dual-band on-body near-field antenna for measuring deep core temperature with a microwave radiometer applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In our previous study [30], it was reported that most studies on measuring deep core temperature with a microwave radiometer did not focus on the antenna, and consequently proposed an on-body antenna for measuring deep core temperature with compact size. However, the problem and limitation of our previous study was that the simulated and measured reflection coefficient results were different.…”
Section: 𝑃 = 𝑘𝑇𝐵mentioning
confidence: 99%
“…In our previous study [30], it was reported that most studies on measuring deep core temperature with a microwave radiometer did not focus on the antenna, and consequently proposed an on-body antenna for measuring deep core temperature with compact size. However, the problem and limitation of our previous study was that the simulated and measured reflection coefficient results were different.…”
Section: 𝑃 = 𝑘𝑇𝐵mentioning
confidence: 99%